2010
DOI: 10.1097/mcg.0b013e3181c29860
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Release Phosphatidylcholine in Chronic-active Ulcerative Colitis

Abstract: We found a saturable dose response of rPC in the treatment of chronic-active ulcerative colitis with effective doses >or=1 g per day; doses of 3 and 4 g seem to be superior in achieving remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 14 publications
2
30
0
2
Order By: Relevance
“…Fatty acid synthase was reported downregulated in UC [51], which could contribute to the reduced phospholipid content. In addition, phospholipase A2 (PLA2) that catalyzes the degradation of PC to lysoPC [52], showed elevated content and activity in animal models of colitis and in actively inflamed colonic mucosa of UC patients compared to the inactively inflamed mucosa and the control [53][54][55][56]. The upregulation of PLA2 is consistent with the higher lysoPC-to-PC ratio in UC despite decreased overall PC content (lysoPC + PC) [57].…”
Section: Discussionsupporting
confidence: 53%
“…Fatty acid synthase was reported downregulated in UC [51], which could contribute to the reduced phospholipid content. In addition, phospholipase A2 (PLA2) that catalyzes the degradation of PC to lysoPC [52], showed elevated content and activity in animal models of colitis and in actively inflamed colonic mucosa of UC patients compared to the inactively inflamed mucosa and the control [53][54][55][56]. The upregulation of PLA2 is consistent with the higher lysoPC-to-PC ratio in UC despite decreased overall PC content (lysoPC + PC) [57].…”
Section: Discussionsupporting
confidence: 53%
“…We also demonstrated that this protective layer could be compromised by NSAIDs and H. pylori-related bacteria [10], the latter findings being translated to humans by Northfield and associates [25]. Furthermore, other groups demonstrated that a similar mechanism of GI phospholipid secretion may occur in the small bowel [26] and colon [27], and that a decrease in colonic mucosal phospholipid concentration and hydrophobicity may contribute to the pathogenesis of ulcerative colitis [28]. These observations led to the exploration of novel therapeutic approaches to gastrointestinal mucosal injury.…”
supporting
confidence: 59%
“…intestinal epithelial cells (iec) interact with the residing microbiota through the cell surface mucous (cSM) layer, both playing essential roles in the maintenance of mucosal homeostasis. 43,44 commensal bacteria interact with intraepithelial lymphocytes, 45 promote tolerogenic dendritic cells (dc) and induce the stimulation of regulatory t cells (treg) and t helper 2 (th2) cells. 12,46 anti-inflammatory cytokines and mediators, such as interleukin (iL) -4, -5, -10, -13 and transforming-growth-factor-β (tGFβ), are released and these molecules help maintain the healthy balance of the intestinal mucosa.…”
Section: The Remarkable Adaptation Of the Colonic Mucosa To Toll-likementioning
confidence: 99%